The effect of pregnancy health literacy on risk perception in pregnancy and pregnancy anxiety - Abdurrahim Uyanik; Gülten Koç; Mesut Ardiç (BMC Pregnancy and Childbirth)
Abstract Background Health literacy during pregnancy is essential for maintaining and improving a healthy life. This study aims to examine the effect of health literacy on pregnancy-related anxiety and risk perception during pregnancy. Methods This was a cross-sectional study. 204 pregnant women (24–37 weeks of gestation) were included in the study. The study data were collected using the descriptive information form, Maternal Health Literacy in Pregnancy Scale, Risk Perception in Pregnancy Scale, and Pregnancy-Related Anxiety Scale. Data were analyzed using Statistical Package for the Social Sciences (SPSS) (IBM SPSS Statistics for Windows, version 26.0. Armonk, NY: IBM Corp.) software and SPSS Amos. Results The average age of the participants was 28.2; the average age at marriage was 22.76; and the average gestational week was 25.93. 38.7% of the participants were high school graduates. According to the study results, there were significant positive relationships between health literacy and pregnancy anxiety during pregnancy (r =.340, p <.01) and negative relationships between risk perception (r = −.212, p <.05). These findings indicate that while increased health literacy is associated with lower risk perception, it may paradoxically be linked to higher pregnancy-related anxiety. Conclusions This study has shown that health literacy can reduce risk perception while increasing pregnancy anxiety. This situation suggests that increasing knowledge should be considered together with anxiety management.